Peningkatan Keterampilan Berbicara Melalui Metode Bercerita pada Mata Pelajaran Bahasa Indonesia - Salekota, Abu Sale; Zainuddin Notanubun; Sarah Sahetapy (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study was motivated by the low speaking skills of third grade students of SD Inpres 1 Buano Utara. The purpose of this study was to improve students' speaking skills through the application of the storytelling method. This research is a Classroom Action Research (PTK) carried out in two cycles with a subject of 30 students. Data collection was done through observation, documentation, and oral test of speaking skills. The results showed an increase in students' speaking skills after the implementation of the storytelling method. This is shown by the increase in the average score of students' oral tests, from 50.4 in the initial test to 70.5 in cycle I, and increased again to 80.3 in cycle II.